The Personal Income Tax - Bird, Richard M. (World Bank, Washington, DC, 2012)
A recent paper argues persuasively that the two basic pillars of taxation in most countries are the income tax and the VAT (Barreix and Roca 2007). The authors argue that the VAT is excellent as a revenue raiser and works best if it is applied in the simplest and most neutral fashion possible that is, on as broad a base as possible and preferably at a uniform rate. Given the relative unimportance of personal income taxes in most developing countries this argument is at first sight perhaps somewhat surprising. Personal income tax (PIT) revenues are often three to four times corporate tax revenues in developed countries, but in developing countries corporate tax revenues usually substantially exceed PIT revenues. As a percentage of gross domestic product (GDP), PIT revenues in developed countries average about seven percent of GDP as compared to about two percent for developing countries. Moreover, as Bird and Zolt (2005) note, in many developing countries personal income taxes often amount to little more than taxes on labor income. At the same time, although little revenue is received from capital income, income taxes often impose high marginal effective rates on investment and hence discourage growth.